Family functioning, peer relationships and life satisfaction among adolescent of low income family - Pai, Farah Syuhada; Arshat, Zarinah (2016)
The purpose of this study is to determine the influences of family functioning and peer relationships towards adolescent life satisfaction among low income families in Malacca. A sample of 304 respondents was selected and information collected using a questionnaire filled out by the respondents. The results from this study showed that there were a significant relationship between family functioning and peer relationships with life satisfaction. The study also showed that there were significant differences in peer relationships and life satisfaction between boys and girls. Moreover, the findings imply that adolescents with higher level of life satisfaction came from families with higher level of family functioning.